The Characters of Children in Alice Walker’s “Everyday Use” and Eudora Welty’s “A Worn Path”: A Comparative Study - muttalib, fuad (International Journal of Language and Literary Studies, 2021)
This article tries to compare between two well-known American short stories, “A Worn Path” by Eudora Welty and “Everyday Use” by Alice Walker, from a comparative perspective. The author of the first of these stories is an African-American novelist, short story writer, poet, and social activist. Alice Walker and the other story is written by an American short story writer, novelist and photographer, who wrote about the American South, Audra Welty. The specific reasons behind choosing these two short stories because they are written by women writers from different cultures, both deal with racial issues, but more importantly is that both include children characters that can add an attribution to be representations of the new African- American generation. Walker’s story includes the characters of two African- American daughters; Maggi and Dee, each of these characters behave in a different way, a behavior which consequently represents a special attitude towards the new generation of African- Americans. While in Welty’s story, we find the character of the grandson of the protagonist, Phoenix, who has a disease which deprived him from his ability to speak. This study analyses how these three characters provide different angles of seeing how the new generation of African- Americans is represented through a comparative outlook.